Emerging pharmaceutical therapies for COPD - Lakshmi SP; Reddy AT; Reddy RC (International Journal of COPD, 2017)
Sowmya P Lakshmi,1,2 Aravind T Reddy,1,2 Raju C Reddy1,2 1Department of Medicine, Division of Pulmonary, Allergy and Critical Care Medicine, University of Pittsburgh School of Medicine, 2Veterans Affairs Pittsburgh Healthcare System, Pittsburgh, PA, USA Abstract: COPD, for which cigarette smoking is the major risk factor, remains a worldwide burden. Current therapies provide only limited short-term benefit and fail to halt progression. A variety of potential therapeutic targets are currently being investigated, including COPD-related proinflammatory mediators and signaling pathways. Other investigational compounds target specific aspects or complications of COPD such as mucus hypersecretion and pulmonary hypertension. Although many candidate therapies have shown no significant effects, other emerging therapies have improved lung function, pulmonary hypertension, glucocorticoid sensitivity, and/or the frequency of exacerbations. Among these are compounds that inhibit the CXCR2 receptor, mitogen-activated protein kinase/Src kinase, myristoylated alanine-rich C kinase substrate, selectins, and the endothelin receptor. Activation of certain transcription factors may also be relevant, as a large retrospective cohort study of COPD patients with diabetes found that the peroxisome proliferator-activated receptor γ (PPARγ) agonists rosiglitazone and pioglitazone were associated with reduced COPD exacerbation rate. Notably, several therapies have shown efficacy only in identifiable subgroups of COPD patients, suggesting that subgroup identification may become more important in future treatment strategies. This review summarizes the status of emerging therapeutic pharmaceuticals for COPD and highlights those that appear most promising. Keywords: pulmonary, PPAR, phosphodiesterase, emphysema, cigarette, mucus